2019
DOI: 10.1371/journal.pntd.0007265
|View full text |Cite
|
Sign up to set email alerts
|

Helminth mediated modulation of the systemic and mycobacterial antigen – stimulated cytokine profiles in extra-pulmonary tuberculosis

Abstract: Background Helminth infections are known to regulate cytokine responses in both pulmonary and latent tuberculosis infection. Whether helminth infections also modulate cytokine responses in extra-pulmonary tuberculosis, specifically tuberculous lymphadenitis (TBL), has not been examined thus far. Methodology Hence, to determine the cytokine profile in helminth-TBL coinfection, we measured the systemic and mycobacterial (TB)–antigen stimulated levels of Type 1, Type 2, Ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 30 publications
1
19
0
3
Order By: Relevance
“…Our previous study had demonstrated that Stronglyoides stercoralis coinfection could modulate cytokine (but not chemokine) responses both systemically and in an antigen-specific manner (12). We had also demonstrated elevated bacterial burdens in that helminth-TBL coinfection (12). We expand our data on those findings and report the influence of filarial coinfection on the cytokine and chemokine response in TBL disease.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Our previous study had demonstrated that Stronglyoides stercoralis coinfection could modulate cytokine (but not chemokine) responses both systemically and in an antigen-specific manner (12). We had also demonstrated elevated bacterial burdens in that helminth-TBL coinfection (12). We expand our data on those findings and report the influence of filarial coinfection on the cytokine and chemokine response in TBL disease.…”
Section: Discussionsupporting
confidence: 62%
“…To our knowledge, our study is the first to examine the bacteriological and immunological outcomes in filaria-TBL coinfections and the second to examine the same in helminth-TBL coinfections in total (12). Our previous study had demonstrated that Stronglyoides stercoralis coinfection could modulate cytokine (but not chemokine) responses both systemically and in an antigen-specific manner (12). We had also demonstrated elevated bacterial burdens in that helminth-TBL coinfection (12).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It is unknown whether an association between the 2 parasites exists, although it seems likely, given their close relationship when both geographical and socioeconomic risk factors are shared. Bearing in mind the regulation of host immune system by S. stercoralis\ , , in case of co‐infection it could affect the response to the protozoan and affect the evolution of CD via an underlying modulation of cytokine responses. In a study of blood donors, it was found that 10.9% of patients with CD were co‐infected with S. stercoralis , presenting a greater proportion of PCR positivity for T. cruzi than patients with negative Strongyloides serology …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to toxoplasmosis, most of helminth infections are characterized by Th2 type immune response with the production of IL‐4, IL‐5, IL‐19 and IL‐13 and eosinophilia, mastocytosis and high IgE levels 24‐27 . Furthermore, helminths have the ability to downregulate Th1 response to microbial pathogens in coinfected hosts 28‐33 . Beyond helminth infection itself, treatment with helminth‐derived antigens regulates immune response in inflammatory disorders, 34‐40 including infectious diseases 41‐43 …”
Section: Introductionmentioning
confidence: 99%